Analysis of the Factors of Delay in the Delivery of Village Fund Accountability Report in the Department of Community and Village Empowerment (PMD) Gunungsitoli City - Hia, Yarni Deslina; Mendrofa, Syah Abadi; Halawa, Odaligoziduhu; Hulu, Fatolosa (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study analyzes the factors causing delays in the submission of Village Fund Accountability Reports (LPJ) at the Community and Village Empowerment Agency (PMD) of Gunungsitoli City. The research employs a qualitative descriptive approach by conducting interviews, observations, and documentation with eight key informants consisting of agency staff and village officials. The findings reveal that the delays are influenced by both internal and external factors. Internal factors include limited human resource capacity, inadequate understanding of reporting regulations, poor time management, and insufficient technical training. External factors consist of limited access to technology and internet networks, complex administrative verification processes, geographical constraints, and inconsistent regulatory changes. These challenges often result in postponed disbursement of subsequent funds, disruption of development programs, and declining public trust in village governance. The study recommends strengthening technical guidance, enhancing administrative efficiency, expanding the use of digital reporting systems, and implementing sanctions and incentives to improve accountability and timeliness. The results highlight the urgent need for integrated solutions to improve transparency, efficiency, and governance in the village financial reporting process.